2011
DOI: 10.1080/01459740.2011.561456
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Negativity in Serodiscordant Relationships: The Absence, Enactment, and Liminality of Serostatus Identity

Abstract: Three decades into the HIV epidemic, one affected group remains largely invisible: HIV-negative people in intimate relationships with HIV-positive people. Their lives are entwined with the everyday realities of HIV, whether emotional, sexual, social, or medical, yet their experiences, meanings, and practices of being HIV-negative in that context are little considered and understood. When they do appear in the HIV literature, they tend to be assigned an identity that is preconceived as inherently different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…First, addressing HIV and related conditions is often prioritized during the visit with HIV-affected couples, likely due to time constraints often facing clinicians serving HIV-affected populations. When seeing an HIV-affected couple together, clinicians should be mindful of the physical and mental health needs of the HIV-negative partners, in order to mitigate a feeling of consuming a "negative space," a phenomenon seen in our study and others (Persson, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…First, addressing HIV and related conditions is often prioritized during the visit with HIV-affected couples, likely due to time constraints often facing clinicians serving HIV-affected populations. When seeing an HIV-affected couple together, clinicians should be mindful of the physical and mental health needs of the HIV-negative partners, in order to mitigate a feeling of consuming a "negative space," a phenomenon seen in our study and others (Persson, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…Many consumers described being judged negatively by health-care providers because of their sexual involvement with an HIV-infected person. Ironically, even in the HIV health-care sector, many expressed feeling nonexistent, associating the word "negative" with its literal meaning (Persson, 2011). The author of the study concluded, "Three decades into the HIV epidemic, one affected group remains largely invisible: HIV-negative people in intimate relationships with HIV-positive people."…”
Section: Introductionmentioning
confidence: 98%
“…The article draws primarily on interviews with HIV‐positive participants. Narratives of HIV‐negative partners in relation to HIV infectiousness have been discussed extensively elsewhere (Persson et al 2006, 2009, Persson 2008, 2010, 2011, Persson and Richards 2008a). The article draws on data collected across all study phases, together with particular focus on the interviews conducted with 18 HIV‐positive participants in 2009.…”
Section: The Studymentioning
confidence: 99%
“…The study commenced in 2004 and was conducted at the The National Centre in HIV Social Research at the University of New South Wales in collaboration with the Heterosexual HIV/AIDS Service NSW, commonly known as Pozhet. The aim of this qualitative, longitudinal cohort study was to build a comprehensive picture of the experiences of living with HIV among this greatly under-researched population in the local epidemic, including issues around diagnosis, stigma, disclosure, health, treatments, services, relationships, and sexual practice (Persson et al 2006Persson 2008Persson , 2010Persson , 2011Richards 2008a, 2008b). Consequently, the scope of the study was much broader than the particular issue considered here.…”
Section: Background and Approachmentioning
confidence: 99%